Uji Stabilitas dan Aktivitas Antioksidan pada Bubuk Jahe Merah Sebagai Minuman Herbal - Widia Anas Tya; Ira Arianti; Rois Indriawan; A. Nova Zulfahmi; Assrorudin Assrorudin (Jurnal Riset, Inovasi, Teknologi & Terapan, 2026)
This study aimed to evaluate the stability and antioxidant activity of red ginger powder (Zingiber officinale var. rubrum) as an herbal drink for relieving menstrual pain (dysmenorrhea). The study employed an experimental method using a Completely Randomized Design (CRD). Red ginger powder was produced through washing, slicing, and drying processes using a cabinet dryer at 70°C. Stability testing included organoleptic evaluation, homogeneity, pH, and viscosity during real-time storage at room temperature. Antioxidant activity was analyzed using the DPPH method by measuring absorbance with a UV-Vis spectrophotometer. The results showed that red ginger powder possessed good antioxidant activity, indicated by a decrease in absorbance values at various sample concentrations. Stability testing revealed changes in aroma becoming more acidic and a decrease in pH from 5 to 3 after storage, while homogeneity and viscosity remained relatively stable. Active compounds such as gingerol in red ginger function as antioxidants capable of inhibiting the formation of prostaglandins, which are responsible for menstrual pain. Based on the findings, red ginger powder has the potential to be developed as a practical, safe, and effective natural herbal product to help relieve dysmenorrhea.